Computing valuation adjustments for counterparty credit risk using a modified supervisory approach - Patrick Büchel; Michael Kratochwil; Daniel Rösch (Review of Derivatives Research, 2020)
Considering counterparty credit risk (CCR) for derivatives using valuation adjustments (CVA) is a fundamental and challenging task for entities involved in derivative trading activities. Particularly calculating the expected exposure is time consuming and complex. This paper suggests a fast and simple semi-analytical approach for exposure calculation, which is a modified version of the new regulatory standardized approach (SA-CCR). Hence, it conforms with supervisory rules and IFRS 13. We show that our approach is applicable to multiple asset classes and derivative products, and to single transactions as well as netting sets.
Keywords: G21; G32; 330; Counterparty credit risk; Credit valuation adjustments (CVA); Credit exposure; Standardized approach for measuring counterparty credit risk exposures (SA-CCR)